TMIC-13. GLIOMA-DRIVEN DENDRITIC CELL DYSFUNCTION AS AN IMMUNE EVASION STRATEGY AGAINST ADOPTIVE CELLULAR THERAPY. (14th November 2022) - Jin, Dan; Dean, Bayli DiVita; Francis, Connor; Font, Laura Falceto; Reid, Alexandra; Figg, John; Sebastian, Mathew; Flores, Catherine
Abstract: BACKGROUND: Our previous studies has developed an adoptive cellular therapy (ACT) against high grade gliomas in both human and murine systems. ACT significantly improves survival in murine models of CNS malignancies. Our studies have shown that efficacy is associated with the observed increase in tumor-associated dendritic cells (DC) which arise from transferred hematopoietic stem cells (HSC). HSC-derived DCs play a pivotal role in mounting the anti-tumor immune response. In this study, we have identified that treatment resistance may be due to glioma-driven dendritic cell dysfunction. We observed significant down regulation of co-stimulatory markers on tumor-associated dendritic cells in mice that escaped ACT and subsequent capacity to activate tumor-reactive T cells.Method: KR158B bearing mice received HSC and tumor reactive T cells one day before 9 Gy irradiation followed by 3 does of BMDC vaccine. Tumor associated DCs were sorted from tumors evaded from ACT and co-cultured with primary KR158B reactive T cells or escaped KR158B reactive T cells. T cell proliferation and interferon gamma were detected for comparison. PCR array was performed to identify dysregulated functional genes.Results and CONCLUSIONS: Functional evidence demonstrated that dendritic cells from resistant tumor had significantly decreased capacity in activating tumor-reactive T cells against either primary KR158B glioma cells or T cells generated to target tumor cells that evaded ACT. Gene expression data showed this may be due to significant decreases in genes associated with co-stimulation, T cell engagement, and antigen presentation.